CURRICULUM RELIABILITY OF SENDRATASIK STUDY PROGRAM ANTICIPATING CURRICULUM CHANGES AND ARTS LEARNING QUALITY IMPROVEMENT IN SCHOOL - Ardipal Ardipal (International Conference on Languages and Arts, 2014)
This research is inspired by the change in the college curriculum, since 2002/2003 from competency based curriculum to curriculum with the Indonesian National Qualification Framework (INQF or mostly known as KKNI in Indonesia) since 2013/2014. In order to accommodate the questions in higher education, on the existence of curriculum at Music, Dance, and Drama (Sendratasik) Study Program at LPTK (Education Institutions) for the last seven years (since 2007) refering to the change of curriculum in the national education system. This research aims to view and examine the reliability of curriculum Sendratasik Study Program of FBS Universitas Negeri Padang (FBS UNP) that has been designed and being implemented. This study is also as the input for the assessment and comparison of the development of art education curriculum. Keywords: Reliability Curriculum, Education Art, Sendratasik